Plastic implementation of the melodic and intonation sphere of music in modern dances - Bugayets, Nataliya; Pinchuk, Olga (Professional Art Education, 2024)
The article attempts to reveal the meaning of the phenomenon of plasticity in musical and choreographic art, particular in modern dance. Methods and methodology. The study used methods of search-analytical, structural-typological, comparative, prognostic and generalizing analysis, which allowed to reveal the meaning of the plastic embodiment of the melodic-intonational sphere of music in modern dances. The scientific novelty lies in the reflection of the phenomenon of plasticity in musical and choreographic art; the isolation of the principles of the plastic embodiment of the melodic-intonational sphere of music in modern dance. The results of the study showed that plasticity is a transmission channel through which the integrative interaction of music and dance occurs. It has been established that modern dance, or contemporary dance, the peculiarity of which is the mixing of all dance languages into a single conglomerate, is a historically conditioned manifestation of the 20th century - the era of revolutionary transformations of the ballet theater, the search for a new plastic language, the emergence of unprecedented choreographic concepts and forms, sometimes awakening interest in music and understanding its laws. The principles of plastic reflection of music in dance, in particular its melodic and intonation sphere, are highlighted. Conclusions. It has been established that the musical poetics of choreography, as a plastic embodiment of the means of musical expressiveness in dance, is based on figurative-plastic and aestheticemotional decoding and choreographic transformation in the process of spatial-temporal deployment of all structural elements of musical language, in particular melody, texture, harmony and polyphony. What is valuable is that the organic fusion of these elements determines the lexical unity and integrity of stage solutions in musical and choreographic form.